SUFI GOVERNANCE : APLIKASI ILMU TASAWUF DALAM PEMERINTAHAN - Akhmad Hasan Saleh (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2015)
Indonesian bureaucracy issues were patched through program reform of the bureaucracy which is a postcrisis demand economic reforms in 1997. Bappenas asserts that other reforms will not be runs well without first reforming government bureaucracy. Bureaucratic reform aims to make the bureaucracy is able to carry out its duties more effi ciently and effectively so that it can be realized clean government and good governance. Bureaucratic reforms initiated by the government it is still not able to fi x the bureaucratic culture, especially presses bureaucratic behavior that tends to corrupt. In other words, the reform of the internal bureaucracy alone is not effective in combating corruption. A source of disease bureaucracy basically can be identifi ed from two loci, namely internal and External. Internal sources derived from the weaknesses and failures the existing system in the bureaucracy itself. Internally, the incidence of corrupt behavior the bureaucracy is also due to weak internal control systems. By hence the necessary tools to change the bureaucratic apparatus as spirituality the prevention and eradication of corruption. This is where the later Sufi governance will be a tool to overcome corruption. Sufi governance solution offered is to lean back on the right monotheism. Because the true monotheism then the bureaucrats in charge of serving the community will carry out their duties in a comprehensive manner; as which ones have been listed in the code of ethics bureaucracy, and he will always see the task as a mandate instead of a means to accumulate wealth and depriving people whom it serves. In addition, many research fi ndings show that spiritual approaches such as those in the Sufi concept of governance can be a solution for the government to eliminate corruption through a spiritual approach.